Editorial: Functional testing in the assessment of return to sports after anterior cruciate ligament reconstruction - Sun, Luning (Ann Transl Med, 2015)
The paper entitled “Functional testing differences in anterior cruciate ligament (ACL) reconstruction patients released versus not released to return to sport” published in the American Journal of Sports Medicine (AJSM) assessed Functional Movement Screen (FMS) and the Lower Quarter Y Balance Test (YBT-LQ) as possible objective tools for evaluating a patient’s readiness to return to sports after ACL reconstruction. The results suggest that many patients clinically cleared continue to have measurable function deficits and that both FMS and YBT-LQ may be used as additional tools for return to sports clearance.